PENGARUH PROMOSI, HARGA, DAN WORD OF MOUTH TERHADAP MINAT BELI PENGGUNA APLIKASI TIKTOK SHOP - Marta, Indri Ani Tri; Nurtantiono, Andri (JURNAL ILMIAH EDUNOMIKA, 2024)
This study aims to analyze the effect of Promotion, Price, and Word of Mouth on Buying Interest of users of the mobile application; TikTok Shop. The population used for the study is the users of TikTok Shop in which the population samples are taken by applying purposive sampling method. The data are obtained by using questionnaires distributed to 97 respondents. Several data analysis techniques are being used for the analysis such as validity test, reliability test, classic assumption test as well as multiple linear regression analysis. The result of the study shows that promotion has no significant effect partially on buying interest, while price and word of mouth significantly affect partially buying interest. In simultaneous testing, the Promotion, Price, and Word of Mouth Variables have influence on Buying Interest.